Effect and Mechanism of Titanium Nanomaterials on Microbial Community Structure and Function in Sequencing Batch Reactor - Pan, Fei; Ye, Yuxuan; Wang, Qinrong; Fu, Jie; Xia, Dongsheng; Liu, Wen (ACS ES&T Water, 2022)
{ A series doses (0–1.0 g/L) of titanium dioxide (TiO2) and titanate nanotubes (TNTs) were added into the sequencing batch reactor (SBR) to investigate the biological effect of titanium nanomaterials. TNTs and TiO2 showed a moderate suppressing effect on SBR performance, while TiO2 seemed to be more toxic. Further, 0.04 g/L TiO2 resulted in significant inhibition on the removal of methylene blue (p < 0.05